Variants of the influence of endogenous uric acid on the blood level of theophylline-sensitive T-lymphocytes can be predicted without error - Igor Popovych; Anatoliy Gozhenko; Igor Bombushkar; Walery Zukow; Oleksandr Sydoruk; Halyna Kovalchuk (Kazimierz Wielki University, 2024)
Background. During the implementation of the project "Physiological activity of uric acid", our group discovered three variants of relationships between changes in uricemia and blood level of theophylline-sensitive CD8+ T-lymphocytes. The aim of this study is to find out the possibility of predicting one or another variants based on the set of initial parameters (predictors) of the patient. Materials and methods. Under an observations were 34 males (23-70 years) and 10 females (33-76 years) with chronic pyelonephritis in the phase of remission. Testing was performed twice - on admission and after 7-10 days of standard balneotherapy on Truskavets Spa. The main object of the study was serum and urine levels of uric acid. Other metabolic, endocrine and immune parameters were determined in the same blood and urine samples. In addition, EEG and HRV was recorded almost synchronously. Results. As a result of discriminant analysis, 23 predictors were selected. Among them, 10 reflect the power spectral density of all 4 EEG rhythms, 2 - EEG entropy, autonomous reactivity, 2 - hormones, 4 - immunity, 2 - metabolism, and another 2 - Popovych's leukocytary indices of Strain and Adaptation. Prediction accuracy is 100%. Conclusion. The uric acid molecule, as a structural analog of methylxanthines and adenosine, exerts effects on neurons, endocrinocytes, and immunocytes, presumably through their adenosine receptors. The nature of the interaction of uric acid and adenosine receptors of theophylline-sensitive CD8+ T-lymphocytes is determined by a certain biochemical and physiological situation.